PERSEPSI MENGENAI MULTIFUNGSI LAHAN SAWAH DAN IMPLIKASINYA TERHADAP ALIH FUNGSI KE PENGGUNAAN NON PERTANIAN - BAMBANG RAHMANTO; BAMBANG IRAWAN; NUR KHOIRIYAH AGUSTIN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Phenomena of paddy field conversion to non agricultural purposes has been worried,especially conversion in Java. Paddy fields have multi functions that related to many aspects,such as economic, socio-cultural, ecological environment, amenity, and national food security.Massive conversion of paddy field will caused externalities. Inadequate appraisal of Paddyfield multi functions become one of determinant factors for speeding up process of paddy fieldconversion. Outcome of this research indicate that both village society and regionaldevelopment stake holder give less appreciation to other elements of Paddy field multifunctions rather than its capacity as food stock and labor absorption. Farmers Appreciation forits function as environmental conservation and intrinsic values of paddy field are varied.Farmers aged, education, and the wide of land cultivation tend to affect positively. Meanwhile,the differences of region characteristic tend to affect the differences of farmers opinion incausal factor of environmental degradation.